Urocortins in heart failure and ischemic heart disease - Boonprasert P. (2014)
Urocortins, a novel member of the corticotrophin-releasing factor (CRF) family, have been shown in animal and human studies to possess several beneficial effects in stress, cardiovascular and renal function, and inflammatory responses via CRF receptors. In the heart, urocortins have been demonstrated to produce cardioprotective effects during ischemia and reperfusion injury. Urocortins have also exerted effects on hemodynamic, endocrine and renal parameters in experimental animal heart failure models. In humans, plasma urocortin levels have been shown to significantly increase in systolic heart failure patients. This growing evidence suggests that urocortins may have a prognostic value as well as being a potential therapeutic treatment for heart failure and myocardial infarction patients. Currently, only a few clinical studies on urocortins are available. In this review article, the role of urocortins in the heart has been summarized. Their possible beneficial roles in heart failure and myocardial infarction have been discussed, based on relevant published articles from both basic and clinical studies available to date. © 2007 Elsevier Ireland Ltd. All rights reserved.